Bermuda - Fortenberry, Brent, author.
1 online resource (235 pages)
Keywords: "This special issue ofPost-Medieval Archaeology, guest edited by Brent Fortenberry (Boston University) and Marley Brown III (The College of William and Mary), celebrates archaeology in Bermuda on the eve of the island's 400th anniversary. The volume presents the diverse nature of contemporary archaeological research on Bermuda, drawing together a wide array of scholars from the disciplines of archaeology, history, material culture studies, heritage and architectural history. The volume seeks to bring about a greater awareness of the island's archaeology and to explore its place within the historic and contemporary Atlantic world."